The evolution of community peer support values: reflections from three UK mental health project teams: The McPin peer support evaluation writing collaborative. (4th May 2022) - Mackay, Tanya; Ahmed, Nisba; Andleeb, Humma; Billsborough, Julie; Currie, Richard; Hazzard, Raj; Haider, Fozia; Iqbal, Naima; Matthews, Ffion; Mesarič, Andreja; Parker, Jennie; Pinfold, Vanessa; et al.
ABSTRACT : Objective: To explore emergent values for community-based peer support in three projects and use of peer research methodology. Background: Peer support refers to the support people with shared lived experiences provide to each other. Its roots are in the civil rights movement, providing alternatives to clinical treatments. This method of support is delivered in different settings, with varying degrees of structure. In this paper, it includes shared experience of mental health issues. Methods: We reviewed interview data from two evaluations and one development project - mental health (n = 69), women-only (n = 40), and maternal mental health (n = 24), respectively. Each project used peer research methods. Peer support values from each project were compared, along with reflections from mostly peer researchers who worked on them (n = 11). Results: Six peer support values emerged and were found to be identifiable and applicable in different contexts. Decisions on facilitation and leadership varied across projects and generated some concerns over professionalisation, including non-peer leadership. Frameworks were viewed as broadly useful, but peer support is heterogenous, and peer researchers were concerned about over-rigid application of guidance. Discussion: We propose caution applying frameworks for peer support. Values must remain flexible and peer-led, evolving in new contexts such as COVID-19. Evaluators have a responsibility to consider any potentially negative consequences of their work and mitigate them. This means ensuring research outputs are useful to the peer support community, and knowledge production is based upon methodologies, such as peer research, that complement and are consistent with the values of peer support itself.